2018
DOI: 10.3389/fimmu.2018.02203
|View full text |Cite
|
Sign up to set email alerts
|

Complement as a Biological Tool to Control Tumor Growth

Abstract: Deposits of complement components have been documented in several human tumors suggesting a potential involvement of the complement system in tumor immune surveillance. In vitro and in vivo studies have revealed a double role played by this system in tumor progression. Complement activation in the cancer microenvironment has been shown to promote cancer growth through the release of the chemotactic peptide C5a recruiting myeloid suppressor cells. There is also evidence that tumor progression can be controlled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 86 publications
0
38
0
Order By: Relevance
“…cGAMP induces modest reactivation in vitro without affecting cell death. Recent achievements in cancer immunotherapy (24)(25)(26) have raised the possibility that the application of immunotherapeutic approaches to other fields, including HIV research, could promote the clearance of the latent HIV-1 reservoir (6,27,28). To evaluate the abilities of immunostimulatory biologic agents to induce the reactivation of HIV-1 provirus and to selectively induce the death of latently HIV-1-infected cells, we first analyzed the effects of three different agonists of innate immunity-the RIG-I agonist M8, previously characterized by our group (29), and the STING agonists cGAMP and c-di-GMP (the cyclic dinucleotide of GMP)-on HIV-1 reactivation in J-Lat 10.6 cells, an in vitro model of HIV-1 latency that contains a green fluorescent protein (GFP) gene substitution in the Nef open reading frame (ORF) (30).…”
Section: Resultsmentioning
confidence: 99%
“…cGAMP induces modest reactivation in vitro without affecting cell death. Recent achievements in cancer immunotherapy (24)(25)(26) have raised the possibility that the application of immunotherapeutic approaches to other fields, including HIV research, could promote the clearance of the latent HIV-1 reservoir (6,27,28). To evaluate the abilities of immunostimulatory biologic agents to induce the reactivation of HIV-1 provirus and to selectively induce the death of latently HIV-1-infected cells, we first analyzed the effects of three different agonists of innate immunity-the RIG-I agonist M8, previously characterized by our group (29), and the STING agonists cGAMP and c-di-GMP (the cyclic dinucleotide of GMP)-on HIV-1 reactivation in J-Lat 10.6 cells, an in vitro model of HIV-1 latency that contains a green fluorescent protein (GFP) gene substitution in the Nef open reading frame (ORF) (30).…”
Section: Resultsmentioning
confidence: 99%
“…The involvement of the complement genes in tumorigenesis has been reported in many cancer types. However, the conclusions are contradictory [23], raising the possibility that whether the complement system plays a positive or negative regulatory role in tumorigenesis depends on the cancer type. Since some components of the complement system have been reported to function independent of complement system in cancers [24], another possibility is that these complement genes repressed by the CHD4/NuRD complex, including C4B, may play a regulatory role in cancer progression independent of complement system.…”
Section: Discussionmentioning
confidence: 99%
“…Further comparison of protein expression profiles between thymoma and TSCC identified several extracellular matrix (ECM) proteins, such as CFD, TIMP1, and VCAN, that are overexpressed in TSCC and involved in complement activation and inflammation process. Complement system was traditionally believed to be associated with recognition of cancer cells and function as an effector to disrupt the cancer cells (Gros et al , ; Kochanek et al , ; Macor et al , ; Potlukova and Kralikova, ; Rambach et al , ; Reis et al , ). However, many recent studies also reported its cancer‐promoting role through continuous inflammation in the tumor microenvironment featured by stromal gathering of growth factors, matrix remodeling proteases, cytokines, and chemokines (de Visser et al , ).…”
Section: Discussionmentioning
confidence: 99%